Understanding employee engagement theory, research, and practice - Byrne, Zinta S. (New York, NY Routledge, 2022)
"Understanding Employee Engagement is a comprehensive source for the science and practice of employee engagement. This book provides a rigorous and objective review of scholarship and empirical research on engagement from around the world. Grounded in theory and empirical research, this book debates the definitions of engagement, provides a thorough evaluation of empirical findings in the engagement field including a focus on international findings, and offers practice implications for organizations. The book is broad, with references and research across disciplines and countries, as well as new sections addressing current challenges, such as virtual engagement, engaging the aging workforce, and perspectives on diversity and inclusion. Employers can learn how to foster an engaged organization, practitioners can learn how to measure, identify, and implement evidence-based solutions to disengagement, and researchers can master the existing engagement literature and begin to study the many propositions and new models the author proposes throughout the book. This book is an essential read for scholars, researchers, practitioners, and business leaders alike for understanding how to measure, identify, and implement evidence-based solutions to foster employee engagement"--
Includes bibliographical references and index.
Keywords: Employee motivation; Employees -- Attitudes; Employees -- Psychology